Charging of macroparticles in a high-voltage vacuum arc sheath - Bizyukov, A.A.; Girka, I.A.; Romashchenko, E.V.; Chibisov, A.D. (Вопросы атомной науки и техники, 2015)
Charging of macroparticles (MPs) in front of the negatively biased surface emitted the secondary electrons due to bombardment by multiply charged ions (MCIs) has been investigated. It was found that MPs can be either reflected or attracted to the substrate depending on the substrate bias. Исследуется зарядка макрочастиц (MЧ) напротив отрицательно заряженной поверхности, испускающей вторичные электроны из-за бомбардировки многозарядными ионами (MЗИ). Было найдено, что MЧ могут либо притягиваться к подложке, либо отталкиваться в зависимости от потенциала подложки. Досліджено зарядження макрочастинок (МЧ) напроти від’ємно зарядженої поверхні, яка випромінює вторинні електрони завдяки бомбардуванню багатократно зарядженими іонами (БЗІ). Було знайдено, що МЧ можуть або притягатися до підкладки, або відштовхуватися в залежності від потенціалу підкладки.